Bridging Social Circles: Need for Cognition, Prejudicial Judgments, and Personal Social Network Characteristics - Curşeu, Petru L.; de Jong, Jeroen P. (Frontiers in Psychology, 2017)
Various factors pertaining to the social context (availability of plausible social contacts) as well as personality traits influence the emergence of social ties that ultimately compose one’s personal social network. We build on a situational selection model to argue that personality traits influence the cognitive processing of social cues that in turn influences the preference for particular social ties. More specifically, we use a cross-lagged design to test a mediation model explaining the effects of need for cognition on egocentric network characteristics. We used the data available in the LISS panel, in which a probabilistic sample of Dutch participants were asked to fill in surveys annually. We tested our model on data collected in three successive years and our results show that people scoring high in need for cognition tend to revolve in information-rich egocentric networks, characterized by high demographic diversity, high interpersonal dissimilarity and high average education. The results also show that the effect of need for cognition on social network characteristics is mediated by non-prejudicial judgments.